The Innovative Application of BIM Technology Analyzed from the Perspective of Intelligent Construction Site - Xiao, Jianxuan (Transactions on Engineering and Technology Research, 2024)
With the continuous development of the construction industry, the concept of smart site is gradually emerging, and building information modeling (BIM), as a key force to promote the construction of smart site, has attracted much attention for its innovative application. This paper focuses on the application of BIM technology in smart construction sites, and comprehensively expounds the changes brought by BIM technology through in-depth theoretical discussion and practical case analysis. The research summarizes the innovative application modes of BIM technology in smart construction sites, including visual planning and design, multi-professional collaborative work, simulation and optimization of construction process, and intelligent quality and safety management. Taking the petition center project of Beijing City Sub-center as an example, the specific application effects and challenges of BIM technology in the whole life cycle of the project are analyzed in detail. At the same time, it points out the shortcomings in the current research field, such as the insufficient integration of BIM technology with other emerging technologies, the lack of professional talents, and the inconsistency of data standards. This paper puts forward strategies including strengthening technology integration, improving talent training system, and establishing unified standards, so as to promote the wider and more effective application of BIM technology in intelligent building sites.